Family Obligation, Parenting, and Adolescent Outcomes Among Mexican American Families. (January 2022) - Yan, Jinjin; Hou, Yang; Shen, Yishan; Kim, Su Yeong
The current study investigates how and under what conditions family obligation benefits Mexican American adolescents' adjustment. The study used two waves of data from 604 Mexican American adolescents (54.3% female, Mage.wave1 = 12.41 years, SD = 0.97) and their parents. Structural equation modeling revealed that both adolescents' and parents' sense of family obligation related to more supportive parenting (i.e., parental monitoring, warmth, and inductive reasoning), which linked to better adolescent adjustment (i.e., sense of life meaning, resilience, and grades). There were parent gender differences: Adolescents' family obligation was more strongly related to their reports of maternal (vs. paternal) parenting. The links also varied across informants for parenting: (a) individuals' sense of family obligation related only to their own perceptions of parenting and (b) there were more evident associations between adolescent-reported (vs. parent-reported) parenting and adolescent outcomes.